Epidemiological evaluation of maternal periodontal status in human immunodeficiency virus seropositive pregnant women in India - Sunkavilli Ravi Kiran; Yudheera Karnam; Bammidi Niharika (Wolters Kluwer Medknow Publications, 2022)
Background: Human immunodeficiency virus (HIV) infection in pregnancy was the most common complication in some developing countries. This has major implications for the management of pregnancy and birth. Periodontal disease in HIV-infected pregnant women leads to a hyperinflammatory state which may have an impact on developing fetus. Aim: The evaluation of gingival and periodontal health in HIV seropositive pregnant women. Methods: A sample of 432 HIV seropositive pregnant women visiting the antiretroviral therapy center from January 2016-December 2016 were included in the present study. Information concerning demographic profile, medical history, and oral health information was recorded in a case sheet pro forma. Several measures of periodontal health such as bleeding on probing, plaque index, pocket depth (PD), and clinical attachment loss were obtained and analyzed by using Chi-square test of independence and P value (P < 0.05, statistically significant). Results: Three hundred and ninety-six participants (91.6%) had gum bleeding on >1 tooth. In gingivitis, the distributions of mild, moderate, and severe gingivitis were about 64 (14.81%), 192 (44.44%), and 140 (32.41%) participants, respectively. Participants without periodontitis (without a single PD ≥4 mm) were about 202 (46.76%). Two hundred and thirty participants (53.2%) had periodontal pockets (≥4 mm) on ≥1 tooth. In periodontitis, the distributions of mild, moderate, and severe periodontitis were 28.70%, 15.74%, and 8.80%, respectively. Conclusion: Ninety-two percent of HIV pregnant women have shown gingival inflammation. Periodontitis was observed in 51% of HIV pregnant women. This observation strengthens the importance of oral health care in HIV-positive pregnant women.